A molecular outflow revealing star formation activity in the vicinity of the HII region G034.8-0.7 and the SNR W44 - Paron, Sergio Ariel (2009)
Aims. This work aims at investigating the molecular gas component in the vicinity of two young stellar object (YSO) candidates identified at the border of the HII region G034.8-0.7 that is evolving within a molecular cloud shocked by the SNR W44. The purpose is to explore signatures of star forming activity in this complex region. Methods. We performed a near and mid infrared study towards the border of the HII region G034.8-0.7 and observed a 90×90 region near 18h 56m 48s , +01◦ 18 45(J2000) using the Atacama Submillimeter Telescope Experiment (ASTE) in the 12CO J = 3−2, 13CO J = 3−2, HCO+ J = 4−3 and CS J = 7−6 lines with an angular resolution of 22. Results. Based on the infrared study we propose that the source 2MASS 18564827+0118471 (IR1 in this work) is a YSO candidate. We discovered a bipolar 12CO outflow in the direction of the line of sight and a HCO+ clump towards IR1, confirming that it is a YSO. From the detection of the CS J = 7−6 line we infer the presence of high density (>107 cm−3) and warm (>60 K) gas towards IR1, probably belonging to the protostellar envelope where the YSO is forming. We investigated the possible connection of IR1 with the SNR and the HII region. By comparing the dynamical time of the outflows and the age of the SNR W44, we conclude that the possibility that the SNR triggered the formation of IR1 is unlikely. On the other hand, we suggest that the expansion of the HII region G034.8-0.7 is responsible for the formation of IR1 through the “collect and collapse” process.